The Potential of Utilising Shared Linguistic Repertoire for Facilitating Interactions in EFL Classrooms - Dery Tria Agustin; Pramugara Robby Yana (Journal of English Language Teaching and English Linguistics, 2023)
Inclusion of linguistic repertoire in the English language classroom has been an issue of ongoing debate among ELT scholars. While some believe in the effectiveness of English-only (monolingual) pedagogy, others view linguistic repertoire as resource that can benefit English language learning. Following a bi/multilingual approach to ELT, this paper reports findings of a qualitative study investigating four Indonesian English-as-a-foreign-language (EFL) teachers’ beliefs and practices, focusing on (1) how the teachers used shared linguistic repertoire during English language instruction and (2) how their uses of shared linguistic repertoire facilitated classroom interactions. Data sources included interviews, classroom observations, and documents. The findings demonstrate that uses of shared linguistic repertoire facilitated both teacher-learner and learner-learner interactions, serving a range of pedagogical functions. This paper concludes by providing implications for teacher education and suggesting areas for future research.